PALAEOMAGNETISM, MAGNETIC STRATIGRAPHY, AND PETROMAGNETISM OF THE UPPER VENDIAN SEDIMENTARY ROCKS IN THE SECTIONS OF THE ZOLOTITSA RIVER AND IN THE VERKHOTINA HOLE, WINTER COAST OF THE WHITE SEA, RUSSIA - Popov V.V.; Khramov A.N.; Bachtadse V. (My University, 2005)
Palaeomagnetic and petromagnetic studies were carried out in two sections of the Late Vendian-Early Cambrian rocks in the southeastern White Sea region. Ninety meters of the Zolotitsa River section (350 oriented lump samples from the outcrops) and 420 m of core samples from the Verkhotina Hole (443 samples) were studied. Two absolute age values are available for the lower part of the Zolotitsa River section: 550 4.6 Ma and 550 5.3 Ma. These ages were determined using zircons from the volcanic rock interlayers. The rocks investigated in this study are characterized by the low anisotropy of magnetic susceptibility, by the absence of any predominant directions of the half-axes of the ellipsoids of anisotropy, and by the planar type of the latter. The main carrier of natural remanent magnetization (NRM) is hematite in all rocks, magnetite being found occasionally in gray rocks. The detailed stepwise thermal demagnetization of the samples proved the multicomponent composition of the rocks. The low- and medium-temperature components resulted from the demagnetization of the rocks during various interval of geologic time. The high-temperature component is characterized by the positive tests of folding, reversal, and correlation, hence being a primary one. Variations of its direction along the rock sequence were used in this study to identify 27 zones of direct and 28 zones of reversed polarity for the total amount of the rocks investigated in this study. The most reliable results were used to plot the alternative trajectory of the Baltic palaeomagnetic pole migration for the Vendian time and to reconstruct the palaeogeographic Baltic position for that time. A new method was offered and tested for orienting borehole samples in space. Its application was found to produce the high convergence of the results, both in the case of the natural outcrops and borehole samples.
Keywords: PALAEOMAGNETISM; MAGNETIC STRATIGRAPHY; PETROMAGNETISM; UPPER VENDIAN; WHITE SEA; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская::Вендский